Back to Basic in Management - T N Hari (Response Books, 2003)
The authors emphasize that organizations must persist in developing fundamental capabilities and that managers need to create new frameworks within which they continually test their strategies, policies and decisions. This unique and well-written book is a salutary and much-needed reminder of the fundamentals of managing any enterprise, while warning against a wholesale and uncritical acceptance of theories, concepts and models.